1997
DOI: 10.1346/ccmn.1997.0450106
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Smectite to Illite In Bentonite and Associated Sediments from Kaka Point, New Zealand: Contrast in Rate and Mechanism

Abstract: Abstract--Smectite and mixed-layer illite/smectite (US) in Triassic heulandite-rich bentonite from Kaka Point, New Zealand, have been investigated by scanning electron microscopy (SEM), transmission electron microscopy/analytical electron microscopy (TEM/AEM) and X-ray diffraction (XRD) for comparison with matrix phyllosilicates in closely associated siltstones and analcimized tuff. Samples that were treated to achieve permanent expansion showed that some smectite in bentonite occurs as curved packets of wavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
(73 reference statements)
3
24
0
Order By: Relevance
“…Several studies have proposed K-fixation in smectite prior to I-S formation (Ahn and Peacor, 1986;Inoue et al, 1987;Li et aL, 1997). Masuda et al (1996) reported K-rich smectite forrmng directly as an alteration product of volcanic glass in silicic ash of the Nankai Trough.…”
Section: Mechanism Of Formationmentioning
confidence: 99%
“…Several studies have proposed K-fixation in smectite prior to I-S formation (Ahn and Peacor, 1986;Inoue et al, 1987;Li et aL, 1997). Masuda et al (1996) reported K-rich smectite forrmng directly as an alteration product of volcanic glass in silicic ash of the Nankai Trough.…”
Section: Mechanism Of Formationmentioning
confidence: 99%
“…The packets are curved and have a diverse morphology. According to Li et al (1997), similar features are typical of the complete alteration of glass shards to smectite.…”
Section: Discussionmentioning
confidence: 97%
“…The limestone contains plagioclase clasts of fine silt and textural features suggestive of calcified glassy clasts. It is overlain by up to 10 cm of bentonite (69241), unusual in containing analcimised rather than heulanditised (Li et al 1997) contains coarse silt-sized clasts of plagioclase An 28-58, minor albite-oligoclase, alkali feldspar and quartz, and copious cuspate glass shards altered to heulandite-K and clinoptilolite-K in a matrix of clay minerals. Analcimic tuffs and analcimic tuffaceous siltstones are prominent, e.g., forming a 6-m zone at 690 m. Siltstones contain sparse silt-sized shards of glass altered to heulandite, others (69152) contain analcime.…”
Section: Tilson Siltstonementioning
confidence: 99%
“…4) but sometimes with the interior consisting of an amorphous clay precursor (Li et al 1997). Less commonly in the bentonites, analcime takes the place of heulandite.…”
Section: Diagenesis Very Low-grade Metamorphism Maturationmentioning
confidence: 99%